A Fuzzy Delphi Approach to Social Cohesion Among Malay Muslims in Malaysia - Amir Hamzah, Nur Anis Amalina; Ishak, Mohd Sobhi; Abdullah, Azlina; Baharuddin, Shamsul Amri; Sarkowi, Azizah; Hassim, Ahmad Zul Hakimi (Millah: Journal of Religious Studies, 2025)
Existing research on social cohesion in Malaysia often examines it at the national level, with a strong emphasis on inter-ethnic relations. However, there is a significant gap in studies th at focus solely on intra-ethnic cohesion within the Malay-Muslims community. This study addresses that gap by developing and validating, through expert consensus, a new instrument to measure intra-ethnic cohesion. The study employs a quantitative design using the Fuzzy Delphi Method with a 7-point Likert scale, involving 10 carefully selected experts. Data were analysed using triangular fuzzy numbers and defuzzification ranking. Findings show that all elements of the proposed construct such as self-belonging, inclusivity, organizational/ political participation, recognition, legitimacy and equality has reached expert consensus. The agreement level exceeded 75%, the threshold value was below 0.2 (d<0.2) and the fuzzy score (A) was greater than the α-cut value of 0.5. These results provide a foundation for developing a structured framework for measuring social cohesion within the Malay-Muslim community in Malaysia. This article reports Phase 1 of instrument development, highlighting its limitations and future directions for full psychometric validation.